Krüppel homolog 1 and E93: The doorkeeper and the key to insect metamorphosis. Issue 3 (6th August 2019) - Belles, Xavier
Abstract: Insect metamorphosis is regulated by two main hormones: ecdysone (20E), which promotes molting, and juvenile hormone (JH), which inhibits adult morphogenesis. The transduction mechanisms for the respective hormonal signals include the transcription factors Krüppel homolog 1 (Kr‐h1) and E93, which are JH‐ and 20E‐dependent, respectively. Kr‐h1 is the main effector of the antimetamorphic action of JH, while E93 is a key promoter of metamorphosis. The ancestral regulatory axis of metamorphosis, which operates in insects with hemimetabolan (gradual) metamorphosis and is known as the MEKRE93 pathway, is based on Kr‐h1 repression of E93. In the last juvenile stage, when the production of JH dramatically decreases, Kr‐h1 expression is almost completely interrupted, E93 becomes upregulated and metamorphosis proceeds. The holometabolan (complete) metamorphosis mode of development includes the peculiar pupal stage, a sort of intermediate between the final larval instar and the adult stage. In holometabolan species, Broad‐Complex (BR‐C) transcription factors determine the pupal stage and E93 stimulates the expression of BR‐C in the prepupa. The MEKRE93 pathway is conserved in holometabolan insects, which have added the E93/BR‐C interaction loop to the ancestral (hemimetabolan) pathway during the evolution from hemimetaboly to holometaboly. Abstract : The MEKRE93 pathway in hemimetabolan and holometabolan metamorphoses.